The influence of work environment on employees' work spirit study at PT. Ultimate Metal Mandala - Tita Rachtawati Santanu (Jurnal Mantik, 2024)
The purpose of this research is to determine the influence of the work environment on the work spirit of study employees at PT. ultimate metal mandala. The research methods used are descriptive and causal associative methods. Data collection techniques in this research are questionnaires, interviews, observation and literature study. Meanwhile, the data analysis techniques used are validity and reliability tests, Correlation Coefficient Test analysis, coefficient of determination and hypothesis testing. Based on the results of research by testing the correlation between Work Environment variables and Work Morale, a Spearman Rank correlation was obtained of 0.649. The correlation coefficient is in the "Strong" interval because it is located in the interval 0.600-0.799, so it can be interpreted that the influence of the Work Environment on Work Morale at PT Mandala Logam Utama has a strong influence. Meanwhile, the magnitude of the influence exerted by the Work Environment and Work Morale can be seen from the coefficient of determination of 0.499 or 49% and the remaining 51% is influenced by other factors which were not researched. Then the results of testing the hypothesis of the influence of the Work Environment on Work Morale obtained a value > equal to 7259 > 2260 and a significant value of 0.00 < 0.10, then it can be concluded that it is rejected and accepted. This means that the work environment has a positive and significant effect on work morale.